2011
DOI: 10.1080/17470218.2011.573080
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Stimulus Dimensions in the Perception of Music

Abstract: A central aim of cognitive psychology is to explain how we integrate stimulus dimensions into a unified percept, but how the dimensions of pitch and time combine in the perception of music remains a largely unresolved issue. The goal of this study was to test the effect of varying the degree of conformity to dimensional structure in pitch and time (specifically, tonality and meter) on goodness ratings and classifications of melodies. The pitches and durations of melodies were presented either in their original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 92 publications
(110 reference statements)
4
40
1
Order By: Relevance
“…Research on goodness ratings of single melodies with similar manipulations to the present experiments found that pitch and time interacted when the main effect sizes (squared semipartial correlations) of the two dimensions were more equal (Prince, 2011). That finding was consistent with an interpretation that interactions between dimensions can become obscured when one dimension is more salient than another ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Research on goodness ratings of single melodies with similar manipulations to the present experiments found that pitch and time interacted when the main effect sizes (squared semipartial correlations) of the two dimensions were more equal (Prince, 2011). That finding was consistent with an interpretation that interactions between dimensions can become obscured when one dimension is more salient than another ).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, sufficiently imbalanced dimensional salience (e.g., via changes in stimulus structure, or task) can obscure otherwise observable pitch-time interactions (Prince, 2011;). Perhaps in this experiment temporal variables were sufficiently stronger than pitch variables so as to suppress any observable interaction between dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have occurred in judgements of melodic similarity (Monahan & Carterette, 1985); participants tended to base similarity ratings on one dimension (pitch or time) at the expense of the other. Some authors have suggested that this ability to emphasise selectively one dimension over another is suggestive of independent processing (Palmer & Krumhansl, 1987a, 1987bPrince, 2011). In any case these data suggest that pitch has a special role in the perception and production of auditory sequences, relative to time.…”
Section: Dimensional Diversity and Pitch Saliencementioning
confidence: 81%
“…The data from Experiment 2 support the notion that framing the debate in this way may constitute an oversimplification (cf. Ellis & Jones, 2009;Prince, 2011;. No interactions emerged between pitch and temporal diversity for any dependent measure, in apparent support of independence.…”
Section: Pitch-time Combinationmentioning
confidence: 91%